2014
DOI: 10.3389/fimmu.2014.00214
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Diversity of the NKR-P1:Clr (Klrb1:Clec2) Recognition Systems

Abstract: The NKR-P1 receptors were identified as prototypical natural killer (NK) cell surface antigens and later shown to be conserved from rodents to humans on NK cells and subsets of T cells. C-type lectin-like in nature, they were originally shown to be capable of activating NK cell function and to recognize ligands on tumor cells. However, certain family members have subsequently been shown to be capable of inhibiting NK cell activity, and to recognize proteins encoded by a family of genetically linked C-type lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 159 publications
1
55
1
Order By: Relevance
“…There exist at least five functional mouse NKR-P1 receptors, three stimulatory isoforms (NKR-P1A,C,F), and two inhibitory isoforms (NKR-P1B,G) (Carlyle et al, 2008;Kirkham and Carlyle, 2014). Originally described almost 40 years ago (Glimcher et al, 1977), the NKR-P1 proteins were the first receptors to be identified as selectively expressed by NK cells.…”
Section: Natural Killer (Nk) Cells Are a Subset Of Innate Lymphoid Cementioning
confidence: 99%
See 2 more Smart Citations
“…There exist at least five functional mouse NKR-P1 receptors, three stimulatory isoforms (NKR-P1A,C,F), and two inhibitory isoforms (NKR-P1B,G) (Carlyle et al, 2008;Kirkham and Carlyle, 2014). Originally described almost 40 years ago (Glimcher et al, 1977), the NKR-P1 proteins were the first receptors to be identified as selectively expressed by NK cells.…”
Section: Natural Killer (Nk) Cells Are a Subset Of Innate Lymphoid Cementioning
confidence: 99%
“…Yet to date, NKR-P1C, the prototypical NK1.1 antigen in B6 mice (Glimcher et al, 1977;Koo and Peppard, 1984;Ryan et al, 1992), and NKR-P1A remain orphan-activating receptors with unknown physiological ligands. On the other hand, the paired NKR-P1F and NKR-P1G receptors recognize overlapping ''self'' Clr (Clec2) ligands to balance signals during NK cell education and effector responses, while the inhibitory NKR-P1B receptor recognizes the broadly expressed self Clr-b (Clec2d) ligand (Carlyle et al, 2004;Chen et al, 2011;Iizuka et al, 2003;Kveberg et al, 2009 been shown to be involved in ''missing-self'' recognition under diverse pathological states (Kirkham and Carlyle, 2014), including cancer (Carlyle et al, 2004), genotoxic and cellular stress (Fine et al, 2010), hematopoietic transplantation , immune escape of primary lymphoma cells , and cytomegalovirus and poxvirus infection Voigt et al, 2007;Williams et al, 2012), while the remainder of the self Clr ligands remain less well characterized. Among pathogens recognized by NK cells, cytomegaloviruses (CMV) demonstrate co-evolution with their natural hosts, likely due to cycles of natural selection for viral versus host fitness.…”
Section: Natural Killer (Nk) Cells Are a Subset Of Innate Lymphoid Cementioning
confidence: 99%
See 1 more Smart Citation
“…The ligands of KLRs are (1) major histocompatibility complex (MHC) class I molecules and relatives, and (2) CLECs. The former members include CD94, the NKG2 subfamily [10], and the Ly49 subfamily [11], and the latter members are the NK receptor-P1 (NKRP1) subfamily [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The ligands of KLRs are (1) major histocompatibility complex (MHC) class I molecules and relatives, and (2) CLECs. The former members include CD94, the NKG2 subfamily [10], and the Ly49 subfamily [11], and the latter members are the NK receptor-P1 (NKRP1) subfamily [12,13]. The NKRP1 subfamily molecules are type II transmembrane glycoproteins, which contain an amino-terminal cytoplasmic domain, a single transmembrane domain followed by a stalk region, and a single extracellular C-type lectin-like domain (CTLD) [13].…”
mentioning
confidence: 99%